2021
DOI: 10.1177/0271678x21992664
|View full text |Cite
|
Sign up to set email alerts
|

Towards blood biomarkers for stroke patients

Abstract: Stroke outcome considerably varies between stroke patients and often cannot be predicted. Now, Gendrun and colleagues investigated the suitability of blood neurofilament light chain proteins (NFL) as a biomarker of neuronal damage. High NFL levels correlated with brain injury, functional outcome and mortality following all major types of stroke. These data raise hope to revolutionize future prognosis and management of stroke patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 10 publications
(12 reference statements)
0
6
0
Order By: Relevance
“…Apart from that, the fact that the neurological outcome poststroke appears to fluctuate considerably between a mild nondisabling type and a more severe type characterized by permanent disability or even death should be considered. Consequently, the utilization of blood biomarkers has emerged as a promising novel tool aimed at reliably forecasting functional outcomes poststroke [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Apart from that, the fact that the neurological outcome poststroke appears to fluctuate considerably between a mild nondisabling type and a more severe type characterized by permanent disability or even death should be considered. Consequently, the utilization of blood biomarkers has emerged as a promising novel tool aimed at reliably forecasting functional outcomes poststroke [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…As pointed out by Rust, 46 the additional pieces of information given by biomarkers like NfL and GFAP, could be useful also to refer patients to more intensive rehabilitation units, and to monitor the efficacy of pharmacological and rehabilitative treatments. These future perspectives could be furtherly boosted combining these biomarkers with others under study, to envisage a multi-biomarker panel for monitoring brain injury/repair.…”
Section: Discussionmentioning
confidence: 99%
“… 1 , 2 , 47 Recently, with the continuous progress of gene‐level research, the differences in the transcriptional process of monocytes after ischemic stroke may be another potential reason for the different tendencies of different subtypes of stroke. 48 In addition, recent studies reported some novel prognostic biomarkers for predicting stroke outcomes, such as circulating immunoregulatory lymphocytes, 49 neurofilament light chain protein, 50 and circulating microRNA. 51 However, we could not adjust them due to the lack of data.…”
Section: Discussionmentioning
confidence: 99%